Foreign aid, infrastructure development and welfare: An intertemporal analysis - Slobodan Djajić (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
This paper examines the welfare implications of foreign aid within the framework of a two-period, two-country model of international trade. It is up to the donor country to decide what fraction of any given aid package is to be made available for the recipient's immediate, period-one consumption, and what part should be allocated for investment in infrastructure that expands the recipient's production possibilities in period two. The focus of the analysis is on the conditions under which both countries agree or disagree on the manner in which the aid funds should be divided between the two options.
Keywords: F35; H41; 330; foreign aid; trade; model; welfare; Entwicklungshilfe; Wohlfahrtseffekt; Infrastrukturinvestition; Selbsthilfeförderung (Entwicklungsländer)